A poluição gerada por máquinas de combustão interna movidas à diesel - a questão dos particulados. Estratégias atuais para a redução e controle das emissões e tendências futuras - Braun Silvana (Química Nova, 2004)
The exhaust emissions of vehicles greatly contribute to environmental pollution. Diesel engines are extremely fuel-efficient. However, the exhaust compounds emitted by diesel engines are both a health hazard and a nuisance to the public. This paper gives an overview of the emission control of particulates from diesel exhaust compounds. The worldwide emission standards are summarized. Possible devices for reducing diesel pollutants are discussed. It is clear that after-treatment devices are necessary. Catalytic converters that collect particulates from diesel exhaust and promote the catalytic burn-off are examined. Finally, recent trends in diesel particulate emission control by novel catalysts are presented.